Rainwater Harvesting Management Systems: A Comprehensive Technical Review - Oluwatusin, Arti Saxena; Chavan, Ashok Uppin (Journal of Progress in Civil Engineering, 2025)
The lack of proper water supply and sanitation services turns the surroundings into polluted, unhealthy and undignified places to live in and degrades water quality in lakes, rivers and seas. Water management is that the activity of designing , developing, distributing and optimum use of water resources under defined water polices and regulations Water management is very much necessary in future development. The need to improve these services is now recognized as a critical component of poverty, reduction as well as being necessary for progress in health, education, and environmental sustainability. Wastewater treatment, water conservation and hygiene play a vital role in providing healthy living conditions for all in a sustainable way.